Ligation of the intersphincteric fistula tract technique in the treatment of anal fistula - Younes, Hassan E. A. (International Surgery Journal, 2017)
Background: Management of anal fistula is a challenging issue in surgical practice. No single technique is appropriate for treatment of all types of fistulas. The aim of this study was to evaluate the efficacy and safety of a new sphincter-sparing technique: ligation of the intersphincteric fistula tract (LIFT) for management of anal fistula. Methods: Over a period of 18 months from January 2015 to June 2016 twenty-one patients (12 males and 9 females) with transsphincteric anal fistula were treated with the LIFT procedure. Patients were followed up for at least six months postoperatively for fistula recurrence, rate of wound healing and effect on fecal continence. Results: Fistula healing rate was (90.5%); recurrence rate was 9.5% in the form of down staging to intersphincteric fistulas. Mean time of healing of intersphincteric wound was 32±7.4 days (ranged from 17 to 58 days). Mean time of healing of the external opening wound was 27±5.8 days (ranged from 19 to 56 days). No postoperative changes in fecal continence. Conclusions: LIFT operation is a safe and effective management of transsphincteric anal fistula, this technique has high healing rate with no effect on fecal continence.